Pastoralism and Climate Change in East Africa - Mung'ong'o, C. G.; Yanda, Pius Z. (Book collections on Project MUSE., 2016)
Pastoralism and Climate Change in East Africa provides systematic and robust empirical investigations on the impact of climate change on pastoral production systems, as well as participating in the ongoing debate over the efficacy of traditional pastoralism. This book is an initial product of the Project Building Knowledge to Support Climate Change Adaptation for Pastoralist Communities in East Africa implemented by the Centre for Climate Change Studies of the University of Dar es Salaam with support from the Open Society Initiative for Eastern Africa. Traditional pastoralism has proved to be a resilient and unique system of adaptations in a dynamic process of unpredictable climatic variability and continuous human interactions with the natural environment in dryland ecosystems. Pastoral adaptations and climate-induced innovative coping mechanisms have strategically been embedded in the indigenous social structures and resource management value systems. Pastoral livelihoods have, nevertheless, become increasingly vulnerable to climate change impacts as a result of prolonged marginalization and harmful external interventions. The negative effect of global climate change has been an added dimension to the already prevailing crisis in the pastoral livelihood system, which is substantially driven by non-climatic factors of internal and external pressures of change such as population growth, bad governance and shrinking rangelands lost to competing activities.